Evaluation of error correction in writing process - Cuong Phu Nguyen (Vietnam Journal of Education, 2019)
It is obvious that English has become a popular language in many countries in the world. As a means of communication, English guarantees better mutual understanding and has become indispensable for most of people around the world. Thus, it is necessary to find out an appropriate and effective methods of giving feedback to help university students improve their English writing skills. The result of this study indicates that using indirect coded feedback in error correction help students make noticeable progress. The students’ positive attitude towards teacher’s feedback (indirect coded feedback) means that they enjoyed using error codes to find and correct their errors. Moreover, their confidence was boosted because error codes motivated them.